True- and pseudo-mitral annular disjunction in patients undergoing cardiovascular magnetic resonance - Kamil Stankowski; Federica Catapano; Dario Donia; Renato Maria Bragato; Pedro Lopes; João Abecasis; António Ferreira; Leandro Slipczuk; Pier-Giorgio Masci; Gianluigi Condorelli; Marco Francone; Stefano Figliozzi (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Mitral annular disjunction (MAD) is a controversial entity. Recently, a distinction between pseudo-MAD, present in systole and secondary to juxtaposition of the billowing posterior leaflet on the left atrial wall, and true-MAD, where the insertion of the posterior leaflet is displaced on the atrial wall both in diastole or in systole, has been proposed. We investigated the prevalence of pseudo-MAD and true-MAD. Methods: This was a retrospective study, including consecutive patients referred to cardiovascular magnetic resonance (CMR). MAD was defined as a ≥1 mm displacement between the left atrial wall-mitral valve leaflet junction hinge and the top of the left ventricular wall, measured from cine-CMR images in the three long-axis views. Pseudo-MAD and true-MAD were defined as the presence of MAD only in systole or both in systole and diastole, respectively. Results: Two hundred and ninety patients (59 [47–71] years; 181/290 men, 62%) were included. Mitral valve prolapse (MVP) and MAD were found in 24/290 (8%) and 145/290 (50%) patients, of which 100/290 (35%) with true-MAD and 45/290 (16%) with pseudo-MAD. In all measurements, systolic MAD extent (2.3 [1.7–3.0] mm) resulted equal to or greater than diastolic MAD extent (2.0 [1.5–2.9] mm). The most frequent MAD location was the inferior wall (117/290, 40%) and the inferolateral wall was the rarest (50/290, 17%). In patients with MVP, the prevalence of MAD was higher (21/24, 88%), mainly driven by a higher prevalence of pseudo-MAD, as the prevalence of true-MAD did not vary significantly in patients with vs without MVP (p = 0.22), except for the inferolateral wall (9/24, 38% vs 20/266, 8%; p < 0.001). The extent of pseudo-MAD was greater in patients with MVP (4.0 [3.0–5.6] mm) than in those without MVP (2.0 [1.5–3.0]; p < 0.001), whereas the extent of true-MAD did not differ significantly (2.5 [2.0–3.2] mm and 1.9 [1.5–2.9] mm; p = 0.06). At the inferolateral wall, the prevalence of pseudo-MAD was 7/24, 29% vs 14/266, 5% (p < 0.001) in patients with vs without MVP. Conclusion: True-MAD was a common imaging finding in patients undergoing CMR, irrespective of MVP. Patients with MVP showed higher prevalence and extent of pseudo-MAD in all locations and true-MAD in the inferolateral wall